Towards an American Indian Indigenous Theology - Tinker, George E. (The ecumenical review, 2010)
An indigenous American Indian theology must respond, first of all, out of the ongoing oppression of Indian communities. This means that our indigenous theologies must be explicitly and unashamedly political. After 500 years of colonialism and conquest, we must begin, in this process, to find ways to reclaim our own indigenous identities. As we struggle theologically with the residual effects of colonialism and conquest, this means that we will struggle to maintain or reclaim our cultures and our languages. We must assure our colonizer/missionary relatives that our peoples were in touch with the Creator long before the European colonialist ancestors brought the gospel of Jesus Christ to us. From this point on, we indigenous peoples must focus on rebuilding our national (indigenous) communities and not on building churches. That should be the substance of our theological reflection today. So our theologies must necessarily deconstruct the theological discourses of the colonialist Euro-Western churches that have missionized and continue to missionize our peoples. This has to be our starting point before we can reconstruct useful ways of organizing our lives together as indigenous communities.